Biosensing Based on Nanoparticles for Food Allergens Detection - Lidia Nazaret Gómez-Arribas; Elena Benito-Peña; María del Carmen Hurtado-Sánchez; María Cruz Moreno-Bondi (Sensors, 2018)
Food allergy is one of the major health threats for sensitized individuals all over the world and, over the years, the food industry has made significant efforts and investments to offer safe foods for allergic consumers. The analysis of the concentration of food allergen residues in processing equipment, in raw materials or in the final product, provides analytical information that can be used for risk assessment as well as to ensure that food-allergic consumers get accurate and useful information to make their food choices and purchasing decisions. The development of biosensors based on nanomaterials for applications in food analysis is a challenging area of growing interest in the last years. Research in this field requires the combined efforts of experts in very different areas including food chemistry, biotechnology or materials science. However, the outcome of such collaboration can be of significant impact on the food industry as well as for consumer’s safety. These nanobiosensing devices allow the rapid, selective, sensitive, cost-effective and, in some cases, in-field, online and real-time detection of a wide range of compounds, even in complex matrices. Moreover, they can also enable the design of novel allergen detection strategies. Herein we review the main advances in the use of nanoparticles for the development of biosensors and bioassays for allergen detection, in food samples, over the past few years. Research in this area is still in its infancy in comparison, for instance, to the application of nanobiosensors for clinical analysis. However, it will be of interest for the development of new technologies that reduce the gap between laboratory research and industrial applications.